Processing of proprioceptive and vestibular body signals and self-transcendence in Ashtanga yoga practitioners - Fiori, Francesca; David, Nicole; Aglioti, Salvatore M. (Frontiers in Human Neuroscience, 2014)
In the rod and frame test (RFT), participants are asked to set a tilted visual linear marker (i.e. a rod), embedded in a square, to the subjective vertical, irrespective of the surrounding frame. People not influenced by the frame tilt are defined as field-independent, while people biased in their rod verticality perception are field-dependent. Performing RFT requires the integration of proprioceptive, vestibular and visual signals with the latter accounting for field-dependency. Studies indicate that motor experts in body-related, balance-improving disciplines tend to be field-independent, i.e. better at verticality perception, suggesting that proprioceptive and vestibular expertise acquired by such exercise may weaken the influence of irrelevant visual signals. What remains unknown is whether the effect of body-related expertise in weighting perceptual information might also be mediated by personality traits, in particular those indexing self-focusing abilities. To explore this issue, we tested field-dependency in a class of body experts, namely yoga practitioners and in non-expert participants. Moreover we explored any link between performance on RFT and self-transcendence, a complex personality construct, which refers to tendency to experience spiritual feelings and ideas. As expected, yoga practitioners (i) were more accurate in assessing the rod’s verticality on the RFT, and (ii) expressed significantly higher self-transcendence. Interestingly, the performance in these two tests was negatively correlated. More specifically, when asked to provide verticality judgments, highly self-transcendent yoga practitioners were significantly less influenced by a misleading visual context. Our results suggest that being highly self-transcendent may enable yoga practitioners to optimize verticality judgment tasks by relying more on internal (vestibular and proprioceptive) signals coming from their own body, rather than on exteroceptive, visual cues.